Effects of recent iv drug use and severity of psychiatric symptoms to antiviral treatment in people who inject drugs - Karabulut, Sercan (Journal of Dependence, 2023)
Objective: People who inject drugs have major contribution to a rise in hepatitis C virus (HCV) infections. Despite efficacy and safety of direct-acting antiviral (DAA) therapies, patients may have difficulties to receive treatment. In this study we aimed to examine the effect of clinical variables in substance users to access to antiviral treatment and the treatment rate. Method: In this retrospective study, we examined the files of 5586 patients who admitted to Outpatient Treatment Center (OTC) between July 2020-April 2021 and files of 121 patients with positive Anti-HCV results were included. All patients had been routinely assessed by Addiction Profile Index (API) and Adult Attention Deficit Hyperactivity Disorder Self-Rating Scale (ASRS).. Results: Of 121 patients, the most used substance was opiate. Because of the insurance restrictions, DAA treatment might be prescribed in only tertiary referral hospitals. All patients had been referred to a tertiary referral hospital. The mean duration from Anti-HCV testing to treatment was 190.3 days. Actively iv substance users were more likely to use substances every day ( 81.5 % vs 41.5%), start using the current substance at younger age (19.1 vs 20.9), have higher total API scores, have higher depression (4.7 vs 3.7), anxiety subscale scores, and ASRS-A scores (11.3 vs 8.3). Actively iv substance users were no more likely to have longer Anti-HCV – treatment duration (100.4 ve 254.5) and have worse treatment completion rates (% 100 vs 67.7). Conclusion: According to research findings, young adults’ expectations to obtain social status and social conformity through the acquisition of a product may affect spending time for online shopping and they may lose control of the use of credit cards..